Utility Function-based Pricing Strategies in Maximizing the Information Service Provider’s Revenue with Marginal and Monitoring Costs - Robinson Sitepu; Fitri Maya Puspita; Anggi Nurul Pratiwi; Icha Puspita Novyasti (Institute of Advanced Engineering and Science, 2017)
Previous research only focus on maximizing revenue for pricing strategies for information good with regardless the marginal and monitoring costs. This paper aims to focus on the addition of marginal and monitoring costs into the pricing strategies to maintain the maximal revenue while introduce the costs incurred in adopting the strategies. The well-known utility functions applied to also consider the consumer’s satisfaction towards the service offered. The results show that the addition costs incurred for setting up the strategies can also increase the profit for the providers rather than neglecting the costs. It is also showed that the Cobb-Douglas utility functions used can enhance the notion of provider to optimize the revenue compared to quasi linear and perfect substitutes.